Comparative assessment of zero emission electric and hydrogen buses in Australia. (January 2022) - Hensher, David A.; Wei, Edward; Balbontin, Camila
Abstract: The pace of direct electrification vs indirect electrification for public transit bus fleets is accelerating internationally. Clear targets have been established by transport policymakers to achieve a zero-emission bus target as early as 2030 in some jurisdictions. Two prominent choices are battery-driven electric buses and fuel-cell electric buses. We draw on evidence on these current and future developments to provide an assessment of the two types of technology on emission reduction, capital, maintenance and energy costs, and other aspects. We apply a decision support system to compare a number of scenarios for different electrification plans of bus fleets using Australian data. Comparing scenarios such as slow versus fast take up and different mixtures of energy technologies in future zero emission fleets provides evidence on the reductions in carbon dioxide emissions and costs in converting a diesel bus fleet to a fully green, at tailpipe, fleet.